Case Report: Multiple peripheral nerve demyelinating lesions and cerebrovascular injury which resulted in extensive cerebral infarction in a XLP1 patient without EBV infection - Li, Jiaxun; Mo, Dongcan; Lv, Luyu; Huang, Fuling; Wu, Binyan; He, Chunjuan; Wu, Hao; Pang, Wenpeng; Li, Yan; Guo, Liping; Luo, Man (Frontiers in Immunology, 2025)
X-linked lymphocytic proliferative disease type 1 (XLP1) is a primary immune deficiency caused by genetic alterations in the SH2D1A gene, exhibiting a wide variety of severe clinical phenotypes and high mortality. We present the case of a 16-year-old male patient diagnosed with XLP1 who suffered from multiple peripheral nerve demyelinating lesions and extensive cerebral infarction, resulting in two consecutive admissions. The onset of symptoms in his first admission were presented with right foot weakness and difficulty walking. The electromyogram findings revealed multiple peripheral nerve damage of bilateral lower limbs, mainly demyelination. Combined with the cerebrospinal fluid tests and medical history, the patient was diagnosed with chronic inflammatory demyelinating multiple radiculopathy (CIDP). After neurological rehabilitation physiotherapy, vitamin B12 supplements and hormonotherapy, the patient’s symptoms improved and he was discharged. Ten days after discharge, he was readmitted with dizziness, lethargy, memory and cognitive decline. Imaging findings included MRI, Arterial spin labeling (ASL) and magnetic resonance spectral (MRS) confirmed that the patient had suffered from a cerebral infarction, the results of follow-up magnetic resonance angiography (MRA) and magnetic resonance vessel wall imaging were consistent with the typical imaging findings of cerebral vasculitis. No EBV infection was detected during his two admissions, which was extremely rare in XLP1 cases. Due to the patient’s guardians declining the hematopoietic stem cell transplantation (HSCT), we were limited to symptomatic and supportive treatments, focusing on improving brain metabolism, and with a transitory stable condition at present. This case expands our understanding of rare XLP1 complications, shows a potential to study on the immune-related mechanism of possibly lymphocytic abnormal proliferation disorder associated with XLP1 involving both peripheral nerves and cerebrovascular, underscores that XLP1 patients should have regular examinations on their central and peripheral nervous system in order to detect early lesions and prevent serious consequences. And we are able to gain valuable experience and lessons from the patient’s disease progression and prognosis.